Synthesis, characterisation and cytotoxic activity evaluation of new metal-salen complexes based on the 1, 2-bicyclo[2.2.2]octane bridge. (19th January 2021) - Milbeo, Pierre; Quintin, François; Moulat, Laure; Didierjean, Claude; Martinez, Jean; Bantreil, Xavier; Calmès, Monique; Lamaty, Frédéric
Graphical abstract: Highlights: New metal salen complexes starting from enantiopure diamine 1 were synthesized. A mechanochemistry approach is reported for the synthesis of the Mn-complex 7 . Mn complex 7 displays cytotoxic activity against HCT116 cell line. Abstract: ( R )-1, 2-Diaminobicyclo[2.2.2]octane was used as a starting material for the preparation, in solution or in a ball mill, of a salen ligand. Five metal salen complexes were prepared in high yield and their cytotoxic activities were evaluated against the Human Colon cancer HCT116 cell lines. The original manganese salen complex displayed the highest activity with a potency 16 fold higher than that of cisplatin, demonstrating the benefit of the bridging backbone compared to other salen systems. An alternative preparation route for this complex by mechanochemistry was also performed.